2001
DOI: 10.1172/jci6749
|View full text |Cite
|
Sign up to set email alerts
|

The prostaglandin E2 EP1 receptor mediates pain perception and regulates blood pressure

Abstract: IntroductionProstaglandin E2 (PGE 2 ) is produced during inflammatory responses, and increased levels of PGE 2 help mediate some of the cardinal features of inflammation, including pain, edema, and fever (1, 2). PGE 2 exerts its effects through interactions with EP receptors, termed EP1-4 (3). Nonsteroidal anti-inflammatory drugs (NSAIDs) act by inhibiting cyclooxygenase (COX) enzymes and thereby inhibiting prostaglandin production. In the context of this putative mechanism of action, direct cause-and-effect r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
142
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(148 citation statements)
references
References 43 publications
(41 reference statements)
6
142
0
Order By: Relevance
“…Other, EP2 receptorindependent mechanisms of inflammatory hyperalgesia appear to be of major relevance only early in the development of inflammation and are most likely peripheral in nature. They probably include the activation of EP1 or prostacyclin (IP) receptors, as demonstrated by the deficits in peripheral inflammatory pain sensitization observed in EP1 receptor-or IP receptor-deficient mice (8,10). It is apparent from our study that neither EP2 nor EP3 receptors contribute to paw swelling or peripheral thermal sensitization.…”
Section: Figurementioning
confidence: 61%
See 1 more Smart Citation
“…Other, EP2 receptorindependent mechanisms of inflammatory hyperalgesia appear to be of major relevance only early in the development of inflammation and are most likely peripheral in nature. They probably include the activation of EP1 or prostacyclin (IP) receptors, as demonstrated by the deficits in peripheral inflammatory pain sensitization observed in EP1 receptor-or IP receptor-deficient mice (8,10). It is apparent from our study that neither EP2 nor EP3 receptors contribute to paw swelling or peripheral thermal sensitization.…”
Section: Figurementioning
confidence: 61%
“…These receptors differ in their tissue distribution, signaling pathways, and physiological functions, which should allow the treatment of inflammatory pain with much greater specificity than currently achievable by the global blockade of PG synthesis via COX inhibitors. Studies performed either in mutant mice lacking individual PG receptors (8)(9)(10) or with synthetic PG receptor ligands (e.g., refs. 11, 12) have not yet provided a coherent picture of which EP receptors are responsible for inflammatory pain sensitization.…”
Section: Introductionmentioning
confidence: 99%
“…PGE2 has both vasodilating and vasoconstricting properties, and EP1 and EP3 may mediate the vasoconstricting action (25,26). Treatment of rats with ONO-8713 resulted in transient and slight reduction in BP at 4 wk as compared with untreated or aspirin-treated rats (P Ͻ 0.05; Table 1).…”
Section: Characteristics Of Experimental Animalsmentioning
confidence: 98%
“…EP1 is coupled to intracellular Ca 2+ mobilization, EP2 and EP4 are coupled to stimulation of adenylate cyclase via Gs protein and EP3 is coupled to inhibition of adenylate cyclase via Gi protein. Studies performed either in mutant mice lacking the individual PG receptors (Stock et al, 2001) or with synthetic EP receptor agonist/antagonist (Nakayama et al, 2002) have not yet provided a coherent picture of which EP receptors are responsible for inflammatory pain. Recently it has been reported that EP4 knockdown with intrathecally delivered short hairpin RNA attenuates inflammation-induced thermal and mechanical behavioral hypersensitivity (Lin et al, 2006), suggesting that EP4 is a potential target for the pharmacological treatment of inflammatory pain.…”
Section: Introductionmentioning
confidence: 99%